Case Report: Mutations in JAK3 causing severe combined immunodeficiency complicated by disseminated Bacille Calmette–Guérin disease and Pneumocystis pneumonia - Pan, Ying; Pan, Hui; Lian, Chunan; Wu, Beiyan; Lin, Jieying; Huang, Guang; Cui, Binglin (Frontiers in Immunology, 2022)
As a form of severe combined immunodeficiency (SCID), JAK3 deficiency can be fatal from severe infections in children, especially after inoculation of live-attenuated vaccines. We report a unique case of JAK3 deficiency with two compound heterozygous JAK3 mutations, complicated by disseminated BCG disease and Pneumocystis pneumonia. A 5-month-old Chinese girl presented with recurring fever and productive cough after BCG vaccination and ineffective antibiotic treatment. Chest CT demonstrated bilateral infiltrations, enlarged mediastinal and axillary lymph nodes, and hypoplasia of thymus. Mycobacterium tuberculosis and Pneumocystis jirovecii were detected from blood samples by sequencing. Acid-fast bacilli were also found from sputum aspirate and gastric aspirate. Lymphocyte subset analyses indicated T-B+NK- immunodeficiency, and gene sequencing identified two heterozygous missense mutations (one unreported globally) in the Janus homology 7 domain of JAK3. The patient received rifampicin, isoniazid, ethambutol, and trimethoprim/sulfamethoxazole and was discharged after improvements but against advice. The patient died at 13 months of age due to severe infections and hepatic damage. SCID should be recognized before inoculation of live-attenuated vaccines in children. Newborn screening for SCID is advocated. Further investigations are needed to better understand the pathogenicity of the variants and molecular mechanism of JH7 domain of JAK3.